Research of external friction and mechanical losses of polymermetallic systems - Шевеля, И. В. (Proceedings of National Aviation University (archive), 1998)
Considered are the interconnections of mechanical losses and coefficients of polymer external friction depending on the temperature. It is proved that mechanical losses are the leading factors determining the type of temperature dependence of the polymer friction coefficient (temperature distribution and intensity of friction coefficient maximum)